The relationship between psychological distress and weight maintenance in weight cycling: mediating role of eating behavior - Wanyang Li; Dan Wang; Hongyu Chen; Yan Liu; Shuyao Dong; Mingyao Sun; Wei Chen (BMC Public Health, 2024)
Abstract Background Obesity is a global public health concern. The goal of this study was to see if eating habits could mediate the relationship between psychological distress and weight maintenance in a population with a history of weight cycling. Methods A 3-month outpatient intervention consisting of a diet and exercise program was provided to 153 participants. Psychological distress, appetite, and behavior were assessed at the beginning and end of the study. Anthropometric measurements were taken at baseline and six months. Results After the structural equation model was developed, it was discovered that the psychological status of people with obesity and weight cycling histories correlated with the weight loss outcome effect (three and six months). This effect was mediated by factors related to eating behavior. Associative psychological factors had a direct effect on eating behavior (three months: β = 0.181, 95% CI: 0.055–0.310; six months: β = 0.182, 95% CI: 0.039–0.332) and appetite had a direct effect on eating behavior (three months: β = 0.600, 95% CI: 0.514–0.717; six months: β = 0.581, 95% CI: 0.457–0.713), both of which were significant (p < 0.01). At three months, psychological distress has a more substantial positive impact on weight change, with eating behavior acting as a partial mediator. At six months, there was no support for appetite’s moderating role in eating behavior. Conclusions The findings suggest that psychological interventions should be strengthened to improve weight loss effectiveness, particularly in participants with a history of weight cycling, making weight loss more complicated and prone to rebound. Clinical trial registration The study has been registered in Clinical Trials (NCT05311462).